Legal Protection of Workers’ Rights in Indonesia’s Tobacco Industry - Fithriatus Shalihah; Andre Wijaya Laksana; Rajali H. Aji (Lembaga Contrarius Indonesia, 2025)
Workers in the tobacco industry face significant legal and occupational safety challenges due to continuous exposure to hazardous chemicals, tobacco dust, and work-related diseases that often remain undetected at early stages. In Indonesia, existing occupational safety and health regulations adopt a general regulatory approach, lack sector-specific standards, and rely on weak supervisory and enforcement mechanisms. This study aims to formulate a sectoral technical regulatory model that specifically governs the control of tobacco dust and chemical exposure in the production process. It also seeks to design an integrated supervisory framework involving multiple institutional actors to enhance accountability and enforcement effectiveness, and to develop a legal culture approach that promotes sustained occupational safety awareness within the cigarette industry. This research applies a normative legal method using statutory and conceptual approaches to analyze the adequacy of the current regulatory framework. The findings demonstrate, first, that Indonesia’s legal protection for tobacco industry workers remains inadequate due to general occupational safety and health regulations, limited supervision, and low levels of legal awareness among workers. Second, comparative analysis shows that countries such as Singapore, Germany, and Japan ensure stronger worker protection through binding sector-specific regulations and effective enforcement systems. Third, this study finds that effective protection for tobacco industry workers requires the adoption of sector-specific occupational safety and health standards, the implementation of integrated multi-actor supervision, and the strengthening of safety culture through structured training programs and secure reporting mechanisms. This study concludes that comprehensive regulatory reform is necessary to ensure effective legal protection and occupational health security in the tobacco industry.